\(\frac{1-\sqrt{2}}{2\sqrt{3}-3\sqrt{2}}\)
\(=\frac{\left(1-\sqrt{2}\right)\left(2\sqrt{3}+3\sqrt{2}\right)}{\left(2\sqrt{3}\right)^2-\left(3\sqrt{2}\right)^2}\)
\(=\frac{2\sqrt{3}+3\sqrt{2}-2\sqrt{6}-6}{12-18}\)
\(=\frac{\sqrt{6}\left(\sqrt{2}+\sqrt{3}-2-\sqrt{6}\right)}{-6}\)
\(=2+\sqrt{6}-\sqrt{3}-\sqrt{2}\)
\(\frac{1-\sqrt{2}}{2\sqrt{3}-3\sqrt{2}}\)
\(=\frac{\left(1-\sqrt{2}\right)\left(2\sqrt{3}+3\sqrt{2}\right)}{\left(2\sqrt{3}\right)^2-\left(3\sqrt{2}\right)^2}\)
\(=\frac{2\sqrt{3}+3\sqrt{2}-2\sqrt{6}-6}{12-18}\)
\(=\frac{\sqrt{6}\left(\sqrt{2}+\sqrt{3}-2-\sqrt{6}\right)}{-6}\)
\(=2+\sqrt{6}-\sqrt{3}-\sqrt{2}\)
Hông chắc !!!